Three different clinical faces of the same histopathological entity: hair follicle nevus, trichofolliculoma and accessory tragus - Yasemin Yuyucu Karabulut; Engin Şenel; Hacı Halil Karabulut; Yasemin Dölek (Sociedade Brasileira de Dermatologia, 2015)
AbstractBACKGROUND:Hair follicle nevus is a rare, congenital hamartoma with follicular differentiation characterized histologically by numerous, tiny, mature hair follicles. Trichofolliculoma, the histopathological features of which are quite similar to those of hair follicle nevus, is also a hamartoma that differs from hair follicle. Accessory tragus is a relatively common, benign congenital abnormality of the external ear with an incidence rate of 1 to 10 per 1,000 live births.OBJECTIVE:This study seeks to assess the discriminatory value of currently available, histological criteria in the differential diagnosis of hair follicle nevus, accessory tragi and trichofolliculoma.METHODS:Twenty-one patients comprising 9 cases of hair follicle nevus, 8 accessory tragi patients and 4 trichofolliculoma cases, were recruited to perform the study.RESULTS:There were 10 males and 11 females in the study group. No significant difference was observed between the three study groups in terms of age, gender or histopathological parameters such as density of hair follicles, subcutaneous fat score and presence of connective tissue framework. Cartilaginous component was seen in 8 cases that were diagnosed as accessory tragi, while central cyst and radiating hair follicles were seen in 4 cases which were diagnosed as trichofolliculoma.CONCLUSION:The results of our study showed that diagnostic discrimination of these diseases could be made only with the clinicopathologic correlation because of their clinical and histopathological similarities.